Monitoring the dressing operation in the grinding process - Aguiar, Paulo R. [UNESP]; Souza, André G.O. [UNESP]; Bianchi, Eduardo C. [UNESP]; Leite, Ricardo R. [UNESP]; Dotto, Fabio Romano Lofrano [UNESP] (Inderscience Publishers, 2009)
This work was based on a methodology of development and experimentation, and involved monitoring the dressing operation by processing the acoustic emission and electric power signals to detect the optimal dressing moment. Dressing tests were performed in a surface grinding machine with an aluminium grinding wheel. Dressing analysis software was developed and used to process the signals collected earlier in order to analyse not only the dressing parameters but also the software's ability to indicate the instant when the dressing operation could be concluded. Parameters used in the study of burn in grinding were implemented in order to ascertain if they would also prove efficient in monitoring dressing. A comparative study revealed that some parameters are capable of monitoring the dressing operation. It was possible to verify the parameters effectiveness that today are utilised in burning to monitor dressing as well as to create new parameters for monitoring this operation. Copyright © 2009, Inderscience Publishers.
Keywords: Acoustic emission; Dressing; Grinding; Monitoring; Acoustic emission testing; Acoustic emissions; Acoustics; Grinding (comminution); Grinding machines; Grinding mills; Wheel dressing; Burn-in; Comparative studies; Electric power; Grinding process; New parameters; Surface grinding machines; Grinding (machining)